Student Teachers’ Perceptions of English Lecturers’ Competences - Umi Rokhyati (Ahmad Dahlan Journal of English Studies, 2015)
AbstractIt is important to know the competence of lecturers because competent lecturers are needed to produce competent graduates. Students are good informant to know the lecturers’ competence because they intensively interact in the classroom. This research is to know the students’ perception of the lecturers’ competence focusing on the level of competence and the strengths and weaknesses of the competence. The result shows that students perceived positively on the pedagogical, personal, and professional competence of the lecturer